Antioral Squamous Cell Carcinoma Effects of Carvacrol via Inhibiting Inflammation, Proliferation, and Migration Related to Nrf2/Keap1 Pathway. (10th June 2021) - Liu, Hui; Xu, Xiaoliang; Wu, Ran; Bi, Lei; Zhang, Chunguang; Chen, Hui; Yang, Yang
Abstract : Objective . To observe the therapeutic effect of Carvacrol on oral squamous cell carcinoma (OSCC) and dissect underlying molecular mechanisms. Methods . Keap1/Nrf2, NALP3, Vimentin, and E-cadherin expression was detected in OSCC and normal oral mucosa (NOM) tissues using immunofluorescence or western blot. When treated with Carvacrol or tert-butylhydroquinone (TBHQ) that activates Nrf2, the expression of Keap1/Nrf2/HO-1, epithelial-mesenchymal transition- (EMT-) related proteins, and NALP3 was examined in OSCC cells. Nrf2 was silenced by treatment with sh-Nrf2 or ML385. After silencing Nrf2 or Carvacrol treatment, cell proliferation and migration were assessed by clone formation and scratch and transwell tests in OSCC cells. Moreover, the expression of Keap1/Nrf2/HO-1, EMT-related proteins, and NALP3 was detected. Results . Keap1/Nrf2, NALP3, Vimentin, and E-cadherin proteins were all significantly upregulated in OSCC than NOM tissues. Carvacrol significantly suppressed Keap1/Nrf2/HO-1 activation. Carvacrol or silencing Nrf2 markedly inhibited the expression of Keap1/Nrf2/HO-1, EMT-related proteins, and NALP3 inflammasome in OSCC cells. Furthermore, clone formation and migration capacities were suppressed following treatment with Carvacrol or Nrf2 depletion. The opposite results were found when there is overexpression of Nrf2. However, Carvacrol distinctly improved the cancer-promoting effect induced by Nrf2 overexpression. Conclusion . Our findings suggested that Carvacrol ameliorated inflammation, proliferation, and migration for OSCC, which was related to inhibition of the Nrf2/Keap1 pathway.